Variations in Mesospheric Neutral Densities from Rayleigh Lidar Observations at Utah State University - Barton David L.; Wickwar Vincent B.; Herron Joshua P.; Sox Leda; Navarro Luis A. (EPJ Web of Conferences, 2016)
A Rayleigh lidar was operated from 1993 to 2004, at the Atmospheric Lidar Observatory (ALO; 41.7°N, 111.8°W) at the Center for Atmospheric and Space Sciences (CASS) on the campus of Utah State University (USU). Observations were carried out on over 900 nights, 729 of which had good data starting at 45 km and going upward toward 90 km. They were reduced for absolute temperatures and relative neutral number densities. The latter at 45 km can be put on an absolute basis by using atmospheric models that go up to at least 45 km. The models’ absolute number densities at 45 km are used to normalize the lidar observations, thereby providing absolute densities from 45 to 90 km. We examine these absolute density profiles for differences from the overall mean density profile to show altitudinal structure and seasonal variations.